2016
DOI: 10.1080/19317611.2016.1199453
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Students' Attitudes Toward Addressing Sexual Health in Their Future Profession: Validity and Reliability of a Questionnaire

Abstract: Method: A cross-sectional online survey (22 items) were distributed to 186 nursing, occupational therapy and physiotherapy students in Sweden, April 2015. Validity and reliability were tested. Results:The construct validity analysis led to three major factors: present feelings of comfortableness, future working environment and fear of negative influence on future patient relations. The construct validity, internal consistency reliability and intrarater reliability showed good results. Conclusion:The SA-SH is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 27 publications
2
68
0
1
Order By: Relevance
“…The two age groups showed significant differences for six items (items 2, 5,9,12,16,21), where students older than 26 years had significantly higher scores ( Table 2).…”
Section: Results For Subgroupsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two age groups showed significant differences for six items (items 2, 5,9,12,16,21), where students older than 26 years had significantly higher scores ( Table 2).…”
Section: Results For Subgroupsmentioning
confidence: 99%
“…The items in the questionnaire can be divided into four different domains, which are presented in boxplots. The analysis of semesters was based on a previous Latent Class Analysis of the SA-SH, consisting of three response patterns based on the total score of the SA-SH [21]. To create a total score, the responses (1-5) were summed up in all 22 variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown a widespread lack of education concerning sexual health and personal attitudes together with the belief that sexual health is not important for persons with disease or disability, which may further problematize promotion of sexual health among healthcare professionals [ 10 , 11 ]. Healthcare professionals and healthcare professional students agree that sexual health could be part of care and rehabilitation for patients, but that they experience lack of education concerning sexual health and communication about sexual health issues [ 12 16 ]. Healthcare students often have a high level of discomfort concerning communicating about sexual issues, implying the importance of sexual health education and communication about sensitive topics [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%